2007
DOI: 10.1111/j.1365-2672.2007.03440.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal array design in optimizing ERIC-PCR system for fingerprinting rat’s intestinal microflora

Abstract: Aims:  The aim of the present study was to rapidly optimize enterobacterial repetitive intergenic consensus (ERIC)‐PCR amplification systems for fingerprinting rat’s intestinal microflora. Methods and Results:  Orthogonal array design and statistic analysis methods were attempted to rapidly optimize ERIC‐PCR reaction system for fingerprinting intestinal microflora. The results showed that variations of the four factors (Mg2+, dNTP, primer and HotstarTaq polymerase concentrations) changed the fingerprinting pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
4
17
1
Order By: Relevance
“…It is suggested that after meticulous optimization, RAPD could be a reliable, sensitive and reproducible assay for the detection of DNA polymorphism in genetic diversity studies (Blixt et al. 2003; Atienzar and Jha 2006; Peng et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that after meticulous optimization, RAPD could be a reliable, sensitive and reproducible assay for the detection of DNA polymorphism in genetic diversity studies (Blixt et al. 2003; Atienzar and Jha 2006; Peng et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These factors have usually been optimized one at a time neglecting the interactions between them (Perry et al. 2003; Peng et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…after centrifugation at 200 × g to remove coarse particles, the supernatants were combined. The cells in the supernatant of feces or intestine were collected and washed twice with PBS by centrifugation at 10,000 × g for 6 min, and the total DNA was isolated following the extraction protocol as described previously [16]. The DNA was checked for integrity by electrophoretic analysis on 1% agarose gel (agarose Le, MDBio, Inc., Taipei, Taiwan) (compared with sizeknown Hind III digested bacteriophage λ DNA, Tiangen, Inc., Beijing, China).…”
Section: Sample Collection and Dna Extractionmentioning
confidence: 99%
“…The number of levels for the other 3 factors is 2. To minimize the number of experiments, a very efficient experimental design, the Taguchi method, was used (Peng et al 2007, Tekade and Chougule 2013, Yang 2002). The orthogonal array that can accommodate the selected factors and levels is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%